RAGAM POLA PUKULAN ALAT MUSIK SENGGAYUNG DI DESA PANGKALAN BUTON KABUPATEN KAYONG UTARA - Sela Heliza; Yudhistira Oscar Olendo; Christianly Yery Silaban (Universitas Tanjungpura, 2021)
AbstractThis research is based on the variety of striking patterns of the Senggayung musical instrument which is unique in its various striking patterns. The research problem, how is the technique of playing the Senggayung musical instrument and how is the pattern of the Senggayung musical instrument. The aim of this research is to describe the technique of playing the Senggayung musical instrument and to describe the various patterns of striking the Senggayung musical instrument. Research methods, descriptive research and musicalological approaches. The research data, the technique of playing the Senggayung musical instrument and the striking pattern of the Senggayung musical instrument. Data collection techniques, namely observation, interviews, and documentation. Data validity test, source and technique triangulation. The data were analyzed by examining and describing the playing techniques and the various patterns of playing the Senggayung musical instrument. The Senggayung musical instrument is played by hitting other Senggayung musical instruments. Has two sound colors, namely